2020
DOI: 10.2113/eeg-2276
|View full text |Cite
|
Sign up to set email alerts
|

Naturally Occurring Asbestiform Minerals in Italian Western Alps and in Other Italian Sites

Abstract: The natural occurrence of asbestos (NOA) in rocks and soil has been known for many years in several areas of the world, differently from the natural presence of asbestiform minerals. In Italy, the mapping of NOA is mandatory according to the 2001 and 2003 regulations. An investigation, not yet concluded, has revealed that in Italy, NOA is represented by chrysotile and tremolite asbestos with minor amounts of actinolite asbestos and anthophyllite asbestos. A field survey conducted in the Italian Western Alps (I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 18 publications
(9 reference statements)
1
5
0
Order By: Relevance
“…Furthermore, the necessity to include a wider set of minerals within the group of investigated fibres clearly emerged when the focus shifted from industrially produced to environmentally occurring asbestos (e.g. Buck et al, 2013 ; Erskine and Bailey, 2018 ; Bloise et al, 2019 ; Belluso et al, 2020 ; Berry et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the necessity to include a wider set of minerals within the group of investigated fibres clearly emerged when the focus shifted from industrially produced to environmentally occurring asbestos (e.g. Buck et al, 2013 ; Erskine and Bailey, 2018 ; Bloise et al, 2019 ; Belluso et al, 2020 ; Berry et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…[7,[34][35][36] Chrysotile asbestos from Balangero belongs to the Balangero serpentinite of the Lanzo Ultramafic Massif, [26] has a typical crystal-chemical formula (Mg 5.81 Fe 2+ 0.15 Al 0.27 Fe 3+ 0.09 Cr 0.01 ) 6.33 (OH) 7.11 Si 3.97 O 10 , [25] and forms bundles of flexible fibrils with splayed ends. [37,38] Pollastri and coworkers [39] found that Fe is mainly substituent for Mg in the octahedral sites, with possible minor tetrahedral Fe. Furthermore, Fe is a constitutive component in balangeroite, a fibrous inosilicate with a gageite-like structure and chemical formula (Mg,Fe 2+ ,Fe 3+ ,Mn 2+ ) 42 O 6 [Si 4 O 12 ] 4 (OH) 40 , which occasionally intergrows with chrysotile from Balangero, accounting for 0.2-1 wt% of the chrysotile extracted.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, greenstone rocks have been intensively mined worldwide and trade for international commerce (Kazan-Allen, 2005) since the past. Nevertheless, since ophiolite rocks represent a main source for asbestos minerals, many studies have pointed out that the substantial exploitation of greenstones could represent a risk to the human health related to the inhalation of potentially containing asbestos fibres (Belluso et al 2020). The term "asbestos" (regulated-asbestos) refers to a group of six fibrous silicate minerals belonging to serpentine (i.e.…”
Section: Introductionmentioning
confidence: 99%